Profile of Allergic Rhinitis Based on Nasal Eosinophil Count, Total Nasal Symptoms Score and Peak Nasal Inspiratory Flow - Bambang S. R.Utomo; Lina Marlina; Fransiskus Poluan; Jurita Falorin; Danny Luhulima; Yunita R.M. B. Sitompul (Fakultas Kedokteran Universitas Kristen Indonesia, 2019)
Abstract Allergic rhinitis (AR) is a symptomatic disorder of the nose induced after allergen exposure by an immunoglobulin E (IgE)-mediated inflammation of the membranes lining the nose. The manifestation of AR can affect patients’ quality of life. The objective of this study was to evaluate the profile of allergic rhinitis patients in term of nasal eosinophil count, total nasal symptom score (TNSS) and peak nasal inspiratory flow (PNIF). Fourteen allergic rhinitis patients were evaluated using the nasal eosinophil count with Wright-Giemsa staining, total nasal symptom score, and PNIF. The study comprised of 6 (42.9%) men, and 8 (57.1%) women with a mean of age 21.15±3.78 years. Participants’ symptoms and characteristics included sneezing (42%), nasal blockage (21.4%), itchy nose (21.4%), and rinorrhea (14.3%) with a mean TNSS of 8.2±1.8. Intermittent AR was found in 14.3% subjects, persistent AR 78.6%, mild AR 21.4%, and moderate-severe AR 78.6%. The mean PNIF was 80±27.46 L/min, and mean eosinophil count of 2.5±1.74. In conclusion, allergic rhinitis patients demonstrated positive nasal eosinophil count with Wright-Giemsa staining, with the majority of them having persistent and moderate-severe RA. They also had nasal airflow impairment, which could affect quality of life.Keywords: allergic rhinitis, eosinophil, nasal airflow, quality of life. Abstrak Rhinitas alergika (RA) merupakan kelainan pada hidung yang diinduksi oleh pajanan alergen yang berhubungan dengan reaksi inflamasi yang diperantarai IgE pada mokusa hidung. Manifestasi RA dapat mempengaruhi kualitas hidup pasien. Tujuan penelitian ini adalah simptomatik evaluasi profil pasien RA dari segi hitung eosinofil nasal, skor total sindrom nasal (TNSS) dan aliran inspirasi nasal (PNIF). Empat belas pasien RA dievaluasi jumlah eosinofil nasal dengan pewarnaan Wright-Giemsa, skor total simtom nasal dan PNIF. Terdapat 6 (42,9%) laki –laki dan 8 (57,1%) perempuan dengan umur rata-rata usia 21,15±3.78 tahun. Simtom dan karakteristik pasien yaitu bersin (42%), sumbatan hidung (21,4%), hidung gatal (21,4%) dan rinorea (14,3%), dengan rata-rata TNSS 8.2±1.8. Rinitas alergika intermiten ditemukan pada 14,3% subyek, yang persisten 78,6%, sedang 21,4% serta sedang-berat 78,6%. Rata-rata PNIF 80±27.46 L/menit, serta rata-rata jumlah eosinofil 2.5±1.74. Dapat disimpulkan pasien RA menunjukkan jumlah eosinofil nasal positif dengan pewarnaan Wright- Giemsa dan kebanyakan memiliki RA yang persisten dengan tingkat sedang-berat. Terdapat juga gangguan aliran udara hidung yang mungkin mempengaruhi kualitas hidup mereka. Kata Kunci: rinitis alergika, eosinofil, aliran udara hidung, kualitas hidung